2000
DOI: 10.1161/01.res.86.7.737
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Mechanics of R403Q Cardiac Myosin Isolated From the Mouse Model of Familial Hypertrophic Cardiomyopathy

Abstract: Abstract-Familial hypertrophic cardiomyopathy (FHC) is an inherited cardiac disease that can result in sudden death in the absence of any overt symptoms. Many of the cases documented to date have been linked with missense mutations in the ␤-myosin heavy chain gene. Here we present data detailing the functional impact of one of the most deadly mutations, R403Q, on myosin motor function. Experiments were performed on whole cardiac myosin purified from a mouse model of FHC to eliminate potential uncertainties ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
191
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(225 citation statements)
references
References 44 publications
(52 reference statements)
27
191
1
Order By: Relevance
“…Compromised coronary flow due to hypertrophy, microvascular dysfunction (42), increased oxidative stress (43), and increased metabolic demands imposed by abnormal biophysical properties of mutant sarcomeres (7,8) are factors that contribute to premature myocyte death and the emergence of focal fibrosis in HCM. Far less is known about mechanisms that expand the extracellular matrix in HCM hearts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compromised coronary flow due to hypertrophy, microvascular dysfunction (42), increased oxidative stress (43), and increased metabolic demands imposed by abnormal biophysical properties of mutant sarcomeres (7,8) are factors that contribute to premature myocyte death and the emergence of focal fibrosis in HCM. Far less is known about mechanisms that expand the extracellular matrix in HCM hearts.…”
Section: Discussionmentioning
confidence: 99%
“…Activated non-myocyte cells may also be derived from circulating cells (14,(46)(47)(48). Alternatively, the enhanced biomechanical forces resulting from sarcomere protein mutations (7,8) could also provide a local mechanism for activating resident non-myocyte cells. Lineage studies are underway to assess the source of activated non-myocyte cells in HCM hearts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The symptoms, including premature death, were similar to those observed in human, thus showing that the rabbit could be a desirable model for studying FHC. The mouse model was also used to understand the basis for the highly malignant phenotype of the p.R403Q mutation (Tyska et al 2000). The work of Tyska et al (2000) revealed that the mutant protein actually exhibits a 2.3-fold higher actin-activated ATPase activity, a 2.2-fold greater average force generation, and a 1.6-fold faster actin filament sliding in the motility assay.…”
Section: Characterization Of Specific Myh7 Mutationsmentioning
confidence: 99%
“…In transgenic models, levels of mutant sarcomere protein expressed within the heart show some correlation with the severity of myocyte dysfunction [57]. Analyses of the mechanics of Arg403Gln myosin derived from heart muscle indicate enhanced actin-activated ATPase activity, increased generated force, and accelerated actin filament sliding [61]. Taken together with data derived from in vitro systems, these findings collectively indicate HCM myosin mutations produce a gain of function.…”
Section: Animal Modelsmentioning
confidence: 91%